The use of safety practices to reduce occupational injury among solid mineral miners in Southwest, Nigeria: an examination of the health belief model - Kareem, Abiodun J.; Kareem, Adesola O.; Owoeye-Lawal, Oluwatosin T.; Aro, Adewale J.; Lawa, Opeyemi A.; Ibekwe, Ogechukwu C.; Ogunromo, Ayodele Y.; Oluwatuyi, Korede O.; Ejiyooye, Toluwalope (International Journal Of Community Medicine And Public Health, 2022)
Background: The mining industry requires measures at reducing the increasing incidence of occupational injury. The behavioural change towards the use of preventive and safety measures are required. The health belief model concept analyses behavioral change towards the use of preventive measures required to reduce occupational injury. The aim of the study was to use the health belief model to describe miners safety practices in Southwest, Nigeria. Methods: A descriptive cross-sectional study using a structured survey was employed. The consenting staff of the mining industry completed a pretested self-administered questionnaire. Data were analysed using descriptive and inferential statistics. The level of significance was taken as p≤0.05. Results: A total of 73 (60.8%) of the respondents had various forms of occupational injury. The self-efficacy (χ2=4.232; p=0.040) had a statistically significant association with occupational injury and was also a predictor (OR=2.3; p=0.042; 95% CI=1.03-4.97) of injury. The factor that positively affects workers use of personal protective equipment was one health belief model component: self-efficacy (χ2=9.509; p=0.009). The socio-demographic factors associated with self-efficacy were age (χ2=4.135; p=0.042) of the respondents, gender (χ2=5.720; p=0.017) and monthly income (χ2=6.047; p=0.014). Conclusions: The conviction to successfully use the personal protective equipment have a better effect on increasing the rate of preventive behaviour among miners.